2012
DOI: 10.4103/0975-1483.104371
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Errors in Handwritten Outpatient Prescriptions in Oman

Abstract: To evaluate and analyze the handwritten outpatient prescriptions and associated error of omissions from four different hospitals in Oman. The study designed was an observational, retrospective and analysis of prescriptions was carried out by table and chart method. A total of 900 prescriptions were collected between April 2009 to July 2010. The type of error of omissions considered in this analysis includes all three important parts of prescriptions, i.e. superscription, inscription, and subscription. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
2
21
2
Order By: Relevance
“…In our study, we also noted that only 0.04% of the drugs were prescribed without mentioning their dosage form. This value is much better than the values obtained by Joshi et al and Al Shahaibi et al which were 21.85% and 23%, respectively [9,16]. We found that only 1.51% of the prescribed drugs in our study were injections.…”
Section: Discussioncontrasting
confidence: 77%
“…In our study, we also noted that only 0.04% of the drugs were prescribed without mentioning their dosage form. This value is much better than the values obtained by Joshi et al and Al Shahaibi et al which were 21.85% and 23%, respectively [9,16]. We found that only 1.51% of the prescribed drugs in our study were injections.…”
Section: Discussioncontrasting
confidence: 77%
“…Type A errors in our study were 48.0%. These findings were similar in Bahrain (31.0%) [11] and Oman (22.11%) studies [12]. In other study, that analyzed mistakes in prescriptions in…”
Section: Discussionsupporting
confidence: 74%
“…Researchers in the study from Saudi Arabia had not found similar results in prescriptions of antibiotics where lack of dose was observed in 18% cases [14]. Inaccuracies in dosing regime in Bahrain study [11] were the same in percentage value as in our study -14%, while in Oman study they were more frequent -18.4% [12].…”
Section: Int Conf Society Health Welfare 2014mentioning
confidence: 35%
“…Lapses in writing whether the drug should be taken before or after food, during day time, or before bedtime will also cause potential harm to the patient or may lead to failure of the treatment. [31] Common prescribing errors such as wrong or inappropriate drug, dose or units, lack of awareness of drug interactions, choosing two drugs belonging to the same class, choosing wrong routes to give medications, infusions with no clear details of diluent, rate, and most importantly calculation errors, especially in pediatric prescriptions. The consequences of all these errors were explained in detail to the students during the educational interventional sessions.…”
Section: Discussionmentioning
confidence: 99%